2012
DOI: 10.1155/2012/651070
|View full text |Cite
|
Sign up to set email alerts
|

Unprotected Sex with Injecting Drug Users among Iranian Female Sex Workers: Unhide HIV Risk Study

Abstract: Purpose. To assess the prevalence and associated factors of unprotected sex with injecting drug users (IDUs) among a sample of female sex workers (FSWs) in Iran. Methods. This cross-sectional study included 144 FSWs who were interviewed as a part of Unhide HIV Risk Study, a national behavioral survey focusing on various high-risk populations, including IDUs, FSWs, and Men who have Sex with Men (MSMs) in 2009. The survey was conducted in eight provinces in Iran using respondent-driven sampling. Participants' so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…During this period, 24.4% of participants had unprotected sex and 30.1% of them sometimes used a condom, 4.7% almost every time, and 40.6% for all instances of vaginal intercourse (18). Another study showed that 19% of female SWs reported at least one occasion of unprotected sex with an injecting drug user in the past one month (19). Fahimfar et al (20) showed that most of the studied 442 SWs (36.2%) were 25 -34 years old, and 14.3% of them illiterate and 31% unemployed.…”
Section: Discussionmentioning
confidence: 94%
“…During this period, 24.4% of participants had unprotected sex and 30.1% of them sometimes used a condom, 4.7% almost every time, and 40.6% for all instances of vaginal intercourse (18). Another study showed that 19% of female SWs reported at least one occasion of unprotected sex with an injecting drug user in the past one month (19). Fahimfar et al (20) showed that most of the studied 442 SWs (36.2%) were 25 -34 years old, and 14.3% of them illiterate and 31% unemployed.…”
Section: Discussionmentioning
confidence: 94%
“…A large body of research has been conducted to assess the risk of HIV among Iranian high-risk populations (11)(12)(13)(14). Few studies have also been carried out to evaluate the different dimensions of mental and physical health status among Iranian PLHIV.…”
Section: Key Messagesmentioning
confidence: 99%
“…Evidence leaves no doubt that women are more vulnerable to HIV/AIDS than men (17,29,30). In this study "partner's condom refusal" was the main reason of condom non-use among women living with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 67%
“…HIV prevalence was 20.2% among a sample of Iranian drug users, and the positives were more likely to be male, share needles, have unsafe sex, and have a history of imprisonment (16). Another study stated that FSWs predictors of unsafe intercourse with people who inject drugs (PWIDs) included higher education, perceived HIV risk, and perceived family intimacy during childhood (17). Condom use among male PWIDs who had sex with men was only 20% during last sexual intercourse (18).…”
Section: Introductionmentioning
confidence: 99%